Maternal Iodine Status During Pregnancy Is Not Consistently Associated with Attention-Deficit Hyperactivity Disorder or Autistic Traits in Children. Issue 6 (14th March 2020) - Levie, Deborah; Bath, Sarah C; Guxens, Mònica; Korevaar, Tim I M; Dineva, Mariana; Fano, Eduardo; Ibarluzea, Jesús M; Llop, Sabrina; Murcia, Mario; Rayman, Margaret P; Sunyer, Jordi; Peeters, Robin P; et al.
ABSTRACT: Background: Severe iodine deficiency during pregnancy can cause intellectual disability, presumably through inadequate placental transfer of maternal thyroid hormone to the fetus. The association between mild-to-moderate iodine deficiency and child neurodevelopmental problems is not well understood. Objectives: We investigated the association of maternal iodine status during pregnancy with child attention-deficit hyperactivity disorder (ADHD) and autistic traits. Methods: This was a collaborative study of 3 population-based birth cohorts: Generation R ( n = 1634), INfancia y Medio Ambiente ( n = 1293), and the Avon Longitudinal Study of Parents and Children ( n = 2619). Exclusion criteria were multiple fetuses, fertility treatment, thyroid-interfering medication use, and pre-existing thyroid disease. The mean age of assessment in the cohorts was between 4.4 and 7.7 y for ADHD symptoms and 4.5 and 7.6 y for autistic traits. We studied the association of the urinary iodine-to-creatinine ratio (UI/Creat) <150 μg/g—in all mother–child pairs, and in those with a urinary-iodine measurement at ≤18 weeks and ≤14 weeks of gestation—with the risk of ADHD or a high autistic-trait score (≥93rd percentile cutoff), using logistic regression. The cohort-specific effect estimates were combined by random-effects meta-analyses. We also investigated whether UI/Creat modified the associations of maternal free thyroxine (FT4) or thyroid-stimulating hormone concentrations with ADHD or autistic traits. Results: UI/Creat <150 μg/g was not associated with ADHD (OR: 1.2; 95% CI: 0.7, 2.2; P = 0.56) or with a high autistic-trait score (OR: 0.8; 95% CI: 0.6, 1.1; P = 0.22). UI/Creat <150 μg/g in early pregnancy (i.e., ≤18 weeks or ≤14 weeks of gestation) was not associated with a higher risk of behavioral problems. The association between a higher FT4 and a greater risk of ADHD (OR: 1.3; 95% CI: 1.0, 1.6; P = 0.017) was not modified by iodine status. Conclusions: There is no consistent evidence to support an association of mild-to-moderate iodine deficiency during pregnancy with child ADHD or autistic traits.